From QCA (Quantum Cellular Automata) to Organocatalytic Reactions with Stabilized Carbenium Ions. Issue 3 (9th April 2016) - Gualandi, Andrea; Mengozzi, Luca; Manoni, Elisabetta; Giorgio Cozzi, Pier
Abstract: What do quantum cellular automata (QCA), "on water" reactions, and SN 1‐type organocatalytic transformations have in common? The link between these distant arguments is the practical access to useful intermediates and key products through the use of stabilized carbenium ions. Over 10 years, starting with a carbenium ion bearing a ferrocenyl group, to the 1, 3‐benzodithiolylium carbenium ion, our group has exploited the use of these intermediates in useful and practical synthetic transformations. In particular, we have applied the use of carbenium ions to stereoselective organocatalytic alkylation reactions, showing a possible solution for the "holy grail of organocatalysis". Examples of the use of these quite stabilized intermediates are now also considered in organometallic chemistry. On the other hand, the stable carbenium ions are also applied to tailored molecules adapted to quantum cellular automata, a new possible paradigm for computation. Carbenium ions are not a problem, they can be a/the solution! Abstract : All roads lead…to carbenium ions ! Taking advantage of suggestions inserted in Mayr's table of reactivity, we have explored the use and generation of tailored carbenium ions for many purposes. In this account, we will illustrate the advantage in using carbenium ions for developing different research fields, from quantum cellular automata to stereoselective SN 1 type reactions.